ECOLOGICAL AND TECHNOLOGICAL ANALYSIS OF MATERIALS FOR 3D-PRINTING - Бовсуновський, Є. О.; Зінченко, Р. О. (Science-based technologies, 2016)
The article analyzes the main materials used for 3D-printing. Particular attention is paid to the study of ecological and technological analysis of the effects of the most widely used material: Polylactic Acid and Acrylonitrile Butadiene Styrene, as well as their professional series and Nylon, Polyethylene Terephthalate, TPE on the environment. The article deals with the characteristic features of the physical properties of materials (material) for their intended purpose, according sharing all the threads into five main groups: standard, flexible, composite, special and supportive. An assessment of the negative impact on the environment of synthetic fibers used for 3D-printing key parameters: the cost of production, energy consumption, service life, the ability to reuse capacity for biodegradable. The article analyzes the characteristics of promising materials for 3D-printing is the least impact on the environment by using SWOT analysis to highlight all the advantages and disadvantages, opportunities and threats. Article built several types of raw materials used for the manufacture of bulk products, according to the intensity of the impact on the environment. Determined that the least impact on the environment makes use of Polylactic Acid.